Sosialisasi Pentingnya Informasi Saat Terdekteksi Covid 19 Dengan Konsntrasi Pada Pengelolaan Sumber Daya Manusi Ditaman Baca Perigi Sawangan Depok - Rahmi Andini S; Whina Ratnawati; Angga Pratama; Wahadi Siamto; Anisa Nurdina (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2022)
The implementation of Community Service (PKM) is one of the applications of the Tri Dharma of Higher Education which in its implementation makes a positive contribution to the community. The implementation of this PKM took the title "Socializing the Importance of Information When Covid 19 Detected With a Concentration on Human Resource Management at the Perigi Sawangan Reading Park, Depok". The location chosen is the Reading Gardens located in the Cinangka-Sawangan area, Depok City. Where this location has a small business or reading park that still requires socializing the importance of getting information related to covid 19. The method used in the implementation of this PKM is a Workshop or Training. Where previously the direct observation stage was carried out to find out the problem appearing at the research site. This training is used to provide an in-depth understanding of the importance of obtaining information related to covid 19 and human resource management, especially the management of human resources in small businesses or perigi reading parks that have been pioneered. and children can understand and apply human resource management quite well. In addition to human resource management training, this opportunity was also given an explanation of matters related to covid 19. The results of Community Service (PKM) went very smoothly and all participants who attended were ensured to get a fairly good understanding of the material. On At the end of the training session participants were also given simple practices to support their understanding of information related to covid 19 and the ability to implement human resource management in small businesses that were already running at the Perigi Reading Park in CinangkaSawangan. As a refinement and ensuring the ability of participants to apply the material optimally, a periodic evaluation phase will be carried out from the team of lecturers and PKM teaching practitioners. Keywords: Socialization, Information, Human Resources.